Discovering emotional honesty through devised theatre. (April 2014) - Hayes, Peter; Cantillon, Peter; Hafler, Max
Summary Background Despite many calls for a focus on supporting the development of doctors as individuals, many curricula are still characterised by an emphasis on the transmission of predefined knowledge, skills and values. Special study modules (SSMs) were introduced to ensure some element of student selection based on personal interests. We present our experience of an SSM designed to introduce students to drama, as a way of exploring the profession of medicine and their own development as doctors. Context We created a 3–week, full‐time SSM, based on a devised theatre model for fourth‐year medical students in an Irish medical school. This article describes the processes and outcomes of our devised theatre SSM. Innovation A devised piece is not a conventional theatre play, but a theatrical event created from the contributions of all participants, based around a central theme. We found that a devised theatre approach helped students to explore personal perspectives on the profession of medicine, healing and their development as doctors. It then allowed them to perform their insights before an audience of their peers. Implications By participating, the students developed an emotional honesty with them‐selves and with each other. They thought and wrote about their chosen profession. They also learned about physical and interpersonal discipline, ethical issues, teamwork and acquired some lifelong skills. Our experience as evidenced by the students' reflective diaries suggests that devised theatre offers potential as a means of encouraging the personal and professional development of medical students.